2016
DOI: 10.3892/mmr.2016.5449
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin inhibits glucose-6-phosphate dehydrogenase activity in HCT 116 cells through acetylation: Identification of aspirin-acetylated sites

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) catalyzes the first reaction in the pentose phosphate pathway, and generates ribose sugars, which are required for nucleic acid synthesis, and nicotinamide adenine dinucleotide phosphate (NADPH), which is important for neutralization of oxidative stress. The expression of G6PD is elevated in several types of tumor, including colon, breast and lung cancer, and has been implicated in cancer cell growth. Our previous study demonstrated that exposure of HCT 116 human colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…This acetyl group has been shown by others to acetylate cytosolic proteins in cultured cells [24–26], but the effects on mitochondrial proteins have not been investigated. First, we measured aspirin-induced acetylation in whole cell extracts.…”
Section: Resultsmentioning
confidence: 99%
“…This acetyl group has been shown by others to acetylate cytosolic proteins in cultured cells [24–26], but the effects on mitochondrial proteins have not been investigated. First, we measured aspirin-induced acetylation in whole cell extracts.…”
Section: Resultsmentioning
confidence: 99%
“…The primary metabolite of aspirin (acetyl SA) SA can bind to plant and human glyceraldehyde 3-phosphate dehydrogenase (GAPDH), which plays a central role in glycolysis and suppresses nuclear translocation [ 35 ]. Similar results showed that aspirin could acetylate and inhibit glucose-6-phosphate dehydrogenase (G6PD), which catalyses the first reaction in the pentose phosphate pathway and is important for the regulation of oxidative stress [ 36 ]. For the mechanism of action in anti-cancer and chemoprevention activities, aspirin and salicylic acid can directly bind to CDK2 and down-regulate cyclin A2/CDK2 proteins [ 37 ] and inhibit CBP and p300 lysine acetyltransferase activity in vitro through direct competition with acetyl-Coenzyme A at the catalytic site [ 38 ].…”
Section: Discussionmentioning
confidence: 96%
“…Beside, recent study showed that aspirin inhibits G6PD activity in CRC cells through acetylation. 32 Additionally, a novel clinical-stage radiosensitizer and chemosensitizer RRx-001 exerts the anti-proliferative effects through inhibiting G6PD activity in human tumor cells. 33 Future study should focus on the development of selective inhibitors for G6PD and the combinatorial effects with clinical chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%